Case Report—Secondary Antibody Deficiency Due to Endogenous Hypercortisolism - Sarcevic, Jelena; Cavelti-Weder, Claudia; Berger, Christoph T.; Trendelenburg, Marten (Frontiers in Immunology, 2020)
Therapeutic corticosteroids have an immunosuppressive function involving several pathways, including lymphocytopenia and hypogammaglobulinemia. While these effects have been well described in patients that received corticosteroids for therapeutic reasons, the effects of endogenous corticosteroids on the immune system are less well understood. Here, we describe a 21-year old patient with hypercortisolism due to an ACTH producing thymic tumor. In this patient, we observed a decrease in some of the immunoglobulin classes, and in specific B and T cell populations that resembled effects caused by corticosteroid treatment. IgG levels were restored following treatment and normalization of the hypercortisolism.